Interpersonal Skill Overview in the Creative Economy Entrepreneurs in Jakarta - Gunawan, Aristo Surya; Cahayani, Ati (Ilomata International Journal of Management, 2024)
Entrepreneurial concept and creative economy both have common key points that are creativity and innovation. Entrepreneurs use their creativity to create innovation in order to win the business competition. Creative economy has shifted the manufacturing era to the information services era that based on human resources. Nowadays creative economy increasingly plays an important role for Indonesian economy which can be seen in its contribution to Indonesian GDP, numbers of job field creation and export value. Interpersonal skills is necessary and crucial to determine successful of the business. This research was aims to observe and analyze the interpersonal skill of entrepreneurs in creative industry in Jakarta. This research was descriptive research with quantitative and qualitative data analysis. Quantitative data was obtained through questionnaires distributed to 150 entrepreneurs in creative industry as respondents in Jakarta and qualitative data obtained through interview to 15 selected respondents. Based on quantitative data, this research showed that according to respondents “leaders who have capability to give direction” was considered as the most important factor of interpersonal skill, while the “ability to influence others” was considered as the most important dimension. Respondents considered those interpersonal skills factor and dimension as the prominent element to determine their success in business. While based on qualitative data showed that no interpersonal skill dimension was considered as the prominent one, but each dimension will be proper for each different circumstance that they encounter.